STUDI KASUS PENERAPAN BIOLOGICAL MATERNAL SOUNDS DAN TERAPI SENTUHAN IBU DALAM STABILISASI KARDIORESPIRATORI PADA BAYI PREMATUR DENGAN RESPIRATORY DISTRESS SYNDROME - Suryani Suryani; Regina Natalia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Premature infants with Respiratory Distress Syndrome (RDS) often experience physiological instability due to immature organ systems and stressful NICU environments. Developmental care interventions are urgently needed to support stabilization and optimize neonatal outcomes. This study aimed to evaluate the application of Biological Mother Sounds combined with Therapeutic Touch in premature infants with RDS. A descriptive case study method was used, involving one premature infant receiving these interventions as part of nursing care. Data were collected through observation of cardiorespiratory parameters and oxygen saturation. The results showed improvement in oxygen saturation, respiratory stability, and reduced signs of distress after intervention. In conclusion, the combination of Biological Mother Sounds and Therapeutic Touch may serve as a supportive, non-invasive nursing intervention to enhance physiological stability in premature infants with RDS..Keywords: Preterm infant; RDS; Biological Maternal Sounds; Maternal touch therapy; Cardiorespiratory stability